2000
DOI: 10.1128/jvi.74.17.7755-7761.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Pore Structure of the Influenza A Virus M 2 Ion Channel by the Substituted-Cysteine Accessibility Method

Abstract: The M 2 ion channel of influenza A virus is a small integral membrane protein whose active form is a homotetramer with each polypeptide chain containing 96-amino-acid residues. To identify residues of the transmembrane (TM) domain that line the presumed central ion-conducting pore, a set of mutants was generated in which each residue of the TM domain (residues 25 to 44) was replaced by cysteine. The accessibility of the cysteine mutants to modification by the sulfhydryl-specific reagents methane thiosulfonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
(38 reference statements)
7
42
0
Order By: Relevance
“…Such architecture is consistent with the findings about the A/M2 channel pore structure (40,41). As the most striking functional difference between A/M2 and BM2 proteins lies in their sensitivity to amantadine, the investigation of the BM2 protein pore structure is essential for the understanding of this difference and may provide insights for the rational anti-viral drugs design.…”
Section: Discussionsupporting
confidence: 70%
“…Such architecture is consistent with the findings about the A/M2 channel pore structure (40,41). As the most striking functional difference between A/M2 and BM2 proteins lies in their sensitivity to amantadine, the investigation of the BM2 protein pore structure is essential for the understanding of this difference and may provide insights for the rational anti-viral drugs design.…”
Section: Discussionsupporting
confidence: 70%
“…Recent crystallographic (13) and NMR (14) studies of the structure of the A/M2 protein have suggested similar mechanisms for proton conduction and activation but quite different mechanisms for inhibition by amantadine. An essential foundation for both of these studies was prior biochemical information about the A/M2 channel, particularly its pore-lining residues (15)(16)(17) and its active oligomeric state (18). Although the active oligomeric state of the BM2 channel is known to be a tetramer (19), the pore-lining residues of the channel have not yet been identified.…”
Section: Sermentioning
confidence: 99%
“…12 , Ser 16 , or Trp 23 . Based on these experimental data, a BM2 transmembrane domain model is proposed.…”
Section: Sermentioning
confidence: 99%
“…Therefore, we performed cysteinescanning mutagenesis for the residues that form the cytoplasmic-proximal ␣-helical turns of the TM domain (42,62). We used the presence of outward currents into alkaline solutions as an indication that the gate was open.…”
Section: Fig 2 Outward Current Of M 2 -W41f Mutant Protein Is Amantmentioning
confidence: 99%